The challenges and potential of value management in local construction industry - Che Mat, Mohd. Mazlan (Universiti Teknologi Malaysia, 1999)
The Malaysian economy has been a star performer over the past few years and indeed is one of the most dynamic economies in Asia. In line with the expanding national economy, the construction industry has grown at a two (2) digit annual growth continuously for many years. Things have suddenly changed since August, 1997. However, Malaysians need to accept the circumstances and to improve our professionalism, capabilities, competitiveness and resilience. This paper discusses the significant contribution resulting from the Value Management applications and how it can contribute to enhance those values. The paper presents Value Management methodology, its potentials and value enhancement attached to it and dispute the perception that Value Management is just another cost cutting technique. Its potential acceptance in Malaysia and construction industry in particular is no easy tasks as a lot of convincing and marketing need to be done and minimise the challenges ahead